Case Report: Successful Use of Extracorporeal Therapies After ECMO Resuscitation in a Pediatric Kidney Transplant Recipient - Rybalko, Andrey; Pytal, Anna; Kaabak, Mikhail; Rappoport, Nadejda; Bidzhiev, Anuar; Lastovka, Vasilii (Frontiers in Pediatrics, 2020)
The combination of extracorporeal membrane oxygenation (ECMO) and extracorporeal blood purification in children is rarely used due to small total blood volumes, risks of hemodynamic instability and a negative association between volume of blood transfusion and patient outcome. To our knowledge, this is the first description of a multimodal extracorporeal detoxication in the setting of ECMO in a post-kidney-transplant child on immunosuppression. We describe a case of a 30-month old child, who was extracorporeally resuscitated after cardiac arrest during kidney transplantation surgery and additionally treated with a number of extracorporeal blood purification methods (plasma exchange, CytoSorb and lipopolysaccharide adsorption) in the setting of immunosuppression therapy. This case report shows the successful use of multimodal extracorporeal therapies for a good patient outcome. The lack of response to CytoSorb therapy might suggest an occult infection and not necessarily failure of treatment.